Some comments on regular and normal bitopological spaces - Dochviri, I. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
Some properties of regular and normal bitopological spaces are established. The classes of sets inheriting the bitopological properties of regularity and normality are found. A theorem on a finite covering of pairwise normal spaces is proved. We also study the behavior of individual multivalued mappings, taking the axioms of bitopological regularity and normality into account.